Generation of Regular and Irregular Waves in Navier-Stokes CFD Solvers by Matching With the Nonlinear Potential Wave Solution at the Boundaries - Choi, Youngmyung; Bouscasse, Benjamin; Seng, Sopheak; Ducrozet, Guillaume; Gentaz, Lionel; Ferrant, Pierre (HAL CCSD, 2018)
International audience